pegegog 2021
DOI: 10.47750/pegegog.11.04.04
|View full text |Cite
|
Sign up to set email alerts
|

Examination of gifted students’ Internet / game addiction and school social behaviors

Abstract: Internet and games can have some adverse effects if used unconsciously. Especially for gifted students, internet and games can be risky and result in addiction due to their cognitive and social characteristics. Since the game and internet addiction conduce to social problems as well. In this vein, the purpose of the study is to examine the internet and game addiction levels of gifted students and their school social behaviors in terms of gender and age variables. In addition, the relationship between computer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…In terms of gender-related differences, most of the reviewed studies revealed that boys were more likely to manifest PMU than girls [60,61,[63][64][65]67,70,71,79,85,86,88,89,91,93,94], and that this trend was reversed in junior high school, whereby PMU became higher in girls [63]. Likely, males and females are involved in different web-mediated activities for different gender-specific motivations depending on the developmental stage they are going through.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In terms of gender-related differences, most of the reviewed studies revealed that boys were more likely to manifest PMU than girls [60,61,[63][64][65]67,70,71,79,85,86,88,89,91,93,94], and that this trend was reversed in junior high school, whereby PMU became higher in girls [63]. Likely, males and females are involved in different web-mediated activities for different gender-specific motivations depending on the developmental stage they are going through.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have observed that PMU increased significantly with higher age and school grade [63,69,71,73,89,93,94]. Therefore, preschool children had lower PMU levels than primary school children [89], while the latter had lower PMU levels than junior high school children [63].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations